Mathematical Modelling in the Teaching of Statistics in Undergraduate Courses - Campos, Celso Ribeiro (2015)
In agreement with the elements of the statistics education theoretical framework, as well as critical education, mathematical modelling allows the possibility of pedagogical projects that value interdisciplinarity and active participation of the student in knowledge construction. In this chapter, we present a scenario that occurred in the statistics discipline of an undergraduate course. We adopt Critical Education practices to discuss global warming, its causes and consequences for society.